Energy conversion between vaulter and pole in relation to the maximal height of the vaulter's center of gravity - Kageyuki, T.; Matsubayashi, T.; Ohyama, B. K.; Kigoshi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
The purpose of this study was to clarify the energy conversion between the vaulter and the pole in relation to the maximal height of the center of the vaulter's gravity (CG) in the pole vault. Eight male vaulters (season record = 5.32±0.36 m) participated in this experiment. The vaulter's energy and the pole energy were calculated based on the three-dimensional coordinates of reflective markers attached to their bodies collected by a motion capture system, and the box reaction force of the pole measured with a force plate. To clarify the interaction between the vaulter and the pole, vaulting was divided into 2 main phases: the "pole bending phase" and the "pole recoiling phase". Additionally, by referring to the phase division used in the practical field, the pole bending phase and the pole recoiling phase were divided into the "drive phase" and "swing phase", and the "rock back phase" and "inverted phase", respectively. The results obtained are summarized as follows: 1. The larger the vaulter's translational kinetic energy (Et) at take-off, the strain elastic energy in the pole (Epole) at maximal pole bending, and Et at pole straight became, the higher the maximal height of CG became. 2. The smaller the increase in the vaulter's potential energy in the drive phase became, the higher the maximal height of CG became. Additionally, when Et at take-off was the control variable, the smaller the decrease in Et in the drive phase became, the higher the maximal height of CG became. 3. The larger the decrease in Et and the increase in Epole in the swing phase became, the higher the maximal height of CG became. 4. The larger the increase in Et in the rock back phase became, the higher the maximal height of CG became. However, when Epole at maximal pole bending was the control variable, the partial correlation coefficient between the change in Et in the rock back phase and the maximal height of CG was not very large (<0.7). 5. The correlation coefficients between the energy change in the vaulter and the pole in the inverted phase and the maximal height of CG were not very large (<0.7). This study clarified that the conversion of Et into Epole was especially strongly related to the maximal height of CG. Furthermore, the characteristic of the energy conversion in relation to the maximal height of CG in the drive phase and the swing phase differed. These results confirmed the practical rationality of the phase division employed.